Fluorinated β-diketonate complexes M(tfac)2(TMEDA) (M = Fe, Ni, Cu, Zn) as precursors for the MOCVD growth of metal and metal oxide thin films. Issue 35 (16th August 2022) - Stienen, Christian; Grahl, Julian; Wölper, Christoph; Schulz, Stephan; Bendt, Georg
Abstract : Novel trifluoroacetylacetonate complexes M(tfac)2 ·TMEDA (M = Fe, Ni, Cu, Zn) were used as precursors for the MOCVD growth of metal and metal oxide thin films. Abstract : Partially fluorinated β-diketonate complexes M(tfac)2 (TMEDA) (M = Fe 1, Ni 2, Cu 3, Zn 4 ; tfac = 1, 1, 1-trifluoro-2, 4-pentanedionate; TMEDA = N, N, N ′, N ′-tetramethylethylenediamine) were synthesized and structurally (sc-XRD) and thermochemically (TGA) characterised. A new polymorph of Fe(tfac)2 (TMEDA) was found. The structural and physicochemical properties of 1–4 were compared with related M(acac)2 (TMEDA) and M(hfac)2 (TMEDA) (acac = 2, 4-pentanedionate, hfac = 1, 1, 1, 5, 5, 5-hexafluoro-2, 4-pentanedionate) β-diketonate complexes to evaluate the effect of the degree of fluorination. A positive effect on the thermal behaviour of the metal acetylacetonates was observed, but no discernible trends. Application of complexes 1–4 as precursors in a MOCVD process yielded either metal (Ni, Cu) or metal oxide thin films (Fe3 O4, ZnO), which were further oxidized to NiO, CuO and α-Fe2 O3 films by calcination in air at 500 °C.